Population fluctuation of Chaetanaphothrips signipennis Bagnall and Amblyseius swirskii Athias-Henriot in a banana crop - Barrezueta-Unda, Salomon Alejandro (2023)
The main pest of banana fruit is Chaetanaphothrips signipennis Bagnall (Thysanoptera:Thripidae). It is known as the banana red spot thrips. Introduced natural enemies such as the mite Amblyseius swirskii Athias-Henriot (Acari:Physeiidae) are one form of control. In this context, the objective was to compare the population fluctuation of C. signipennis and A. swirskii in banana during 12 weeks after the introduction of the mite. In a 66.40 ha banana plantation, 250 mites were applied to all freshly bagged bunches. Then, a 6 ha plot was delimited and divided into three sections (beginning, middle and end). In each section, 60 plants between 1.30 and 1.60 m tall were randomly selected. Chaetanaphothrips signipennis was counted between the borders of the interior of the petioles, as well as A. swirskii, where it feeds on the thrips of interest. The sum of the populations per week was very heterogeneous, C. signipennis totaled 1,147 thrips, lower than the A. swirskii record of 4,860 mites. The populations of C. signipennis decreased from the second week but increased again in week 11, unlike A. swirskii which increased every two weeks. The population distribution of C. signipennis in the three plots was aggregated. The largest population was concentrated between the middle and the end of the plots. The distribution of A. swirskii was different. It showed a homogeneous distribution in all plots. No relationship was found between temperature, which varied from 26.6 to 29.0 °C at the time of counting.